Gut Microbial-Related Choline Metabolite Trimethylamine-N-Oxide Is Associated With Progression of Carotid Artery Atherosclerosis in HIV Infection - Shan, Zhilei (J Infect Dis, 2018)
We examined associations of 5 plasma choline metabolites with carotid plaque among 520 HIV-infected and 217 HIV-uninfected participants (112 incident plaque cases) over 7 years. After multivariable adjustment, higher gut microbiota-related metabolite trimethylamine-N-oxide (TMAO) was associated with an increased risk of carotid plaque in HIV-infected participants (risk ratio = 1.25 per standard deviation increment; 95% confidence interval, 1.05–1.50; P = .01). TMAO was positively correlated with biomarkers of monocyte activation and inflammation (sCD14, sCD163). Further adjustment for these biomarkers attenuated the association between TMAO and carotid plaque (P = .08). Among HIV-infected individuals, plasma TMAO was associated with carotid atherosclerosis progression, partially through immune activation and inflammation.